The Global Financial Crisis (2007-2008) and Banks’ Liquidity Creation.‘Evidence from UK banks’ - Shahatit, Salma (2011)
The theory of financial intermediation states that liquidity creation has been the main source of risk for banks. This points out to a possible correlation between banks’ liquidity creation and financial crisis. It is believed that that the period preceding the recent Global Financial Crisis (2007-2008) was characterised by abundant liquidity, excessive lending due to deterioration of lending standards and trend towards securitisation. This study attempts to examine empirically this possible correlation by studying the behaviour of liquidity creation of major UK banks/ building societies around the crisis, over the period 2001-2010 using the recently developed measure by Berger and Bouwman (2007). Further, the relationship between bank capital and liquidity creation is empirically tested to verify which alternative hypothesis ‘Financial fragility-crowding out’ or ‘Risk absorption’ dominates the relationship in case of UK banks.